A randomized controlled trial of psychoanalytic psychotherapy or cognitive-behavioral therapy for bulimia nervosa. - Poulsen, S; Lunn, S; Daniel, S; Folke, S; Mathiesen, B; Katznelson, H; Fairburn, C (2014)
OBJECTIVE: The authors compared psychoanalytic psychotherapy and cognitive-behavioral therapy (CBT) in the treatment of bulimia nervosa. METHOD: A randomized controlled trial was conducted in which 70 patients with bulimia nervosa received either 2 years of weekly psychoanalytic psychotherapy or 20 sessions of CBT over 5 months. The main outcome measure was the Eating Disorder Examination interview, which was administered blind to treatment condition at baseline, after 5 months, and after 2 years. The primary outcome analyses were conducted using logistic regression analysis. RESULTS: Both treatments resulted in improvement, but a marked difference was observed between CBT and psychoanalytic psychotherapy. After 5 months, 42% of patients in CBT (N=36) and 6% of patients in psychoanalytic psychotherapy (N=34) had stopped binge eating and purging (odds ratio=13.40, 95% confidence interval [CI]=2.45-73.42; p<0.01). At 2 years, 44% in the CBT group and 15% in the psychoanalytic psychotherapy group had stopped binge eating and purging (odds ratio=4.34, 95% CI=1.33-14.21; p=0.02). By the end of both treatments, substantial improvements in eating disorder features and general psychopathology were observed, but in general these changes took place more rapidly in CBT. CONCLUSIONS: Despite the marked disparity in the number of treatment sessions and the duration of treatment, CBT was more effective in relieving binging and purging than psychoanalytic psychotherapy and was generally faster in alleviating eating disorder features and general psychopathology. The findings indicate the need to develop and test a more structured and symptom-focused version of psychoanalytic psychotherapy for bulimia nervosa.